Clinical-pharmacological drug information center of Hannover Medical School: experiences and analysis from a tertiary care university hospital - Johannes Heck; Dirk O. Stichtenoth; Ruxandra Sabau; Christoph Schröder; Stefan Engeli; Thorben Pape; Nina O’Connell; Carsten Schumacher; Olaf Krause; Felix Koop (Scientific Reports, 2022)
Abstract Drug information centers (DICs) are institutions dedicated to provide objective, independent, and up-to-date information on drugs and their rational use. To overcome the lack of recent DIC reports from central Europe, we analyzed all queries (n = 594) submitted to the DIC run by the Institute for Clinical Pharmacology of Hannover Medical School between October 2018 and April 2022. Approximately one in three queries (31.1%; 185/594) was submitted by internists. 82.8% (492/594) of the queries were patient-specific, while the remaining 17.2% (102/594) were general queries. Adverse drug reactions (ADRs), indications/contraindications, and pharmacodynamic interactions (PDIs) represented the three most frequently addressed query categories, being involved in 44.8% (266/594), 43.3% (257/594), and 34.3% (204/594) of all queries, respectively (assignment of more than one category per query was possible). As compared to general queries, patient-specific queries were statistically significantly more often related to ADRs, PDIs, and pharmacokinetic interactions (PKIs) (ADRs: 35.3% vs. 46.7%, P = 0.034; PDIs: 14.7% vs. 38.4%, P < 0.001; PKIs: 20.6% vs. 31.5%, P = 0.028). To demonstrate the complexity of queries submitted to the clinical-pharmacological DIC, we present and comment on an illustrative selection of queries.